role of intermediaries in sectoral innovation systems: The case of Mongolian information technology sector - Batkhuyag Dashdondov; Sonintamir Nergui; Lodoiravsal Choimaa; Oyundari Ganzorig; Narantsetseg Purevjav (Proceedings of the Mongolian Academy of Sciences)
This paper analyses the types of innovation intermediaries that have emerged in Mongolia and investigates their roles within the information technology sector of the country. The study finds that diverse innovation intermediaries have emerged, and the majority of the intermediaries are non-sector specific, with only a few specializing in a single industry. The sector-specific intermediary plays a crucial role in building linkages and providing access to resources in sectoral innovation systems in developing countries. The study identifies several constraints related to funding and innovation policy support for these intermediaries. Consistent policy and financial support for sector-specific intermediary organizations could strengthen their role in the developing countries, particularly those with limited human and capital resources, such as Mongolia.